Legal Protection of E-Commerce User Privacy in Indonesia from The Perspective of Civil Law and Islamic Law - Mohammad Rafi Arradhiya; Hanifah Febriani (Universitas Muhammadiyah Surakarta, 2025)
E-commerceis an online buying and selling activity mediated by digital devices, facilitating transactions between marketers and consumers. The increasing privacy violations require strong privacy protection laws globally. Data breaches pose risks such as financial loss and identity theft, so raising awareness about data security is essential among governments, companies, and individuals. The methodology used by the author in this study is a doctrinal approach called normative juridical. This normative juridical framework is an established process that aims to achieve the objectives of the study, starting with the utilization of secondary data. In Indonesia, the right to privacy is constitutionally recognized and detailed in the 1945 Constitution and several laws, such as the ITE Law and the PDP Law. Although these laws outline the right to privacy for e-commerce users, they do not have explicit provisions for the resolution of civil disputes related to privacy violations. The analysis includes possible legal remedies under the Civil Code, which allows claims against e-commerce companies for negligence. In addition, it emphasizes consumer protection under the Consumer Protection Law, which, although recognizing rights, does not explicitly mention the right to privacy in the context of e-commerce. The study also explores the Islamic perspective on privacy, where respect for personal data is essential, advocating fairness and transparency in transactions. Ultimately, the conclusion underscores the need for progressive alignment and enforcement of laws to effectively address the issue of privacy violations in e-commerce. Furthermore, it highlights the need to align Islamic legal principles with existing regulations to ensure a comprehensive legal framework that protects privacy rights in the evolving digital marketplace.